UJI STABILITAS FISIK LOTION ANTI NYAMUK KOMBINASI MINYAK LAVENDER (Lavandula angustifolia) DAN MINYAK ROSEMARY (Rormarinus officinalis) - Sari, Devi Amelia; Ambari, Yani; Ningsih, Arista Wahyu; Rahmawati, Dewi (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2023)
Lavender essential oil 15% can be used as an anti-mosquito protection power on average 56% at 6 hours. Rosemary has a more fragrant aroma and can make mosquitoes uncomfortable and avoid it. This study aims to determine physical stability of mosquito repellent lotion. Lavender oil mosquito repellent lotion (Lavandula angustifolia) and rosemary oil (Rosmarinus officinalis) made in 3 formulas, namely F1 containing lavender oil (10%), F2 (15%), and F3 (20%), and F1 containing rosemary oil (30%), F2 (25%), and F3 (20%). Mosquito repellent lotion was tested for its physical stability using the cycling test method which included organoleptic, homogeneity, pH, adhesion, and spreadability. In this research, citronella and lavender oils can be formulated into anti-mosquito lotions. The results of physical stability (organoleptic, pH, homogeneity, spreadability and adhesion) using the cycling test method show that the anti-mosquito lotion did not change during storage and the results were in accordance with the expected specifications. It can be concluded that the difference in the concentration of lavender and rosemary essential oils does not affect the stability test of the anti-mosquito lotion preparation.